Lysosomal protease cathepsin D is a prognostic marker in endometrial cancer. - Lösch, A. (Nature Publishing Group, 1996)
The present study investigates the prognostic value of immunohistochemically detected cathepsin D expression in endometrial adenocarcinoma. Patients with surgically treated endometrial adenocarcinoma FIGO stages I-III and consecutive irradiation therapy were included in the study. When we performed immunohistochemistry to detect cathepsin D in 115 tissue specimens 35 cases showed a positive reaction. In the univariate analysis cathepsin D expression showed significant prognostic value for overall survival (P-value = 0.007). In the multivariate analysis with established prognostic parameters (stage, grade) we found an independent prognostic value for cathepsin D (P-value = 0.002, relative risk = 3.8, 95% confidence interval 1.4 - 10.0). Immunohistochemical detection of cathepsin D could aid in predicting prognosis and planning therapy for patients with endometrial adenocarcinoma. IMAGES: